Dispersion of single-wall carbon nanotubes with supramolecular Congo red – properties of the complexes and mechanism of the interaction - Jagusiak, Anna; Piekarska, Barbara; Pańczyk, Tomasz; Jemioła-Rzemińska, Małgorzata; Bielańska, Elżbieta; Stopa, Barbara; Zemanek, Grzegorz; Rybarska, Janina; Roterman, Irena; Konieczny, Leszek (Beilstein Journal of Nanotechnology, 2017)
A method of dispersion of single-wall carbon nanotubes (SWNTs) in aqueous media using Congo red (CR) is proposed. Nanotubes covered with CR constitute the high capacity system that provides the possibility of binding and targeted delivery of different drugs, which can intercalate into the supramolecular, ribbon-like CR structure. The study revealed the presence of strong interactions between CR and the surface of SWNTs. The aim of the study was to explain the mechanism of this interaction. The interaction of CR and carbon nanotubes was studied using spectral analysis of the SWNT–CR complex, dynamic light scattering (DLS), differential scanning calorimetry (DSC) and microscopic methods: atomic force microscopy (AFM), transmission (TEM), scanning (SEM) and optical microscopy. The results indicate that the binding of supramolecular CR structures to the surface of the nanotubes is based on the "face to face stacking". CR molecules attached directly to the surface of the nanotubes can bind further, parallel-oriented molecules and form supramolecular and protruding structures. This explains the high CR binding capacity of carbon nanotubes. The presented system – containing SWNTs covered with CR – offers a wide range of biomedical applications.
Keywords: Congo red; single-wall carbon nanotubes; supramolecular compounds